Desain Pendidikan Inklusi di Masa Pandemi Covid-19 - Hartin Kurniawati; Ika Rahayu Satyaninrum; Fifin Ari Astutik (Jurnal Dirosah Islamiyah, 2021)
This study aims to determine the design of inclusive education during the COVID-19 pandemic. The research method used is a qualitative approach. In conducting research, data sources are needed, in data collection using primary and secondary sources. Primary sources are data sources that are obtained directly from informants, in this case the principal and homeroom teacher and special companion teachers. Meanwhile, secondary data is in the form of several documents required for completeness of research data. The data analysis technique used is descriptive qualitative through data reduction, data presentation and drawing conclusions. The results showed that inclusive education served all the needs of students regardless of differences. This can be seen from: (1) the composition of the class consists of various aspects of diversity, (2) each student is given treatment according to their needs, (3) SPMB is based on the child's age and observations of student development are made, (4) implements a modified K13 curriculum with the Nature school curriculum that is modified according to the needs of students, (5) learning develops aspects: cognitive, language, physical-motor, social-emotional, and moral and (6) learning evaluation is carried out every day and once a week, (7) Learning during a pandemic is through video calls, WhatsApp with a duration of 1 hour and uses the question and answer method and demonstrations.